Developing cognitive test based on the revised Bloom’s taxonomy on the structure and cell function material for XI grade students in senior high school of Tarakan city - Zulfadli Zulfadli (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
This research was to develop a cognitive test tool based on Revised Bloom’s Taxonomy. This study aimed to determine the quality of the test based on experts assessment, to measure the level of validity, reliability, and to determine the difficulty levels of the questions, discrimination power, and distractors. This research employed Research and Development (R&D) method. The development test model used was the 4D procedure which was modified into three steps: define, design, and develop. The subjects were the Science students of XI grade at SMAN 2 Tarakan and SMA Muhammadiyah Tarakan.  The results of the study were: (1) the experts validation analysis showed that the cognitive test has been categorized as  valid which the value was 4.28 (2) The quality of cognitive test  were: (A) the 90% items were valid, while 10% were invalid. (B) the reliability value was 0.79 (highly reliable) (C) the levels of difficulty were: easy (27%), moderate (53%), difficult (20%). (D)the test discrimination index were: weak (10%), sufficient (33%), good (53%), and either once (3%). (E) distractors effectiveness: effective category (85%), ineffective (15%). Assessment results from expert validators and empirical tests indicate that this cognitive test device is feasible to use and apply. The uniformity of this level of difficulty makes the quality of items were good to use. The discrimination power of these test tool, which has good value, indicate that the high diversity of items is able to measure students' abilities.